2023
DOI: 10.3390/jpm13020333
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers as Prognostic Predictors and Therapeutic Guide in Critically Ill Patients: Clinical Evidence

Abstract: A biomarker is a molecule that can be measured in a biological sample in an objective, systematic, and precise way, whose levels indicate whether a process is normal or pathological. Knowing the most important biomarkers and their characteristics is the key to precision medicine in intensive and perioperative care. Biomarkers can be used to diagnose, in assessment of disease severity, to stratify risk, to predict and guide clinical decisions, and to guide treatments and response to them. In this review, we wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 148 publications
0
19
0
1
Order By: Relevance
“…Furthermore, in cardiac surgery patients, besides the operational stress itself, the additional use of the stressful extracorporeal circuit triggers an unavoidable major immune response, accelerated through the contact of the blood products and the surfaces of the CPB tubes. Additionally, during anesthesia and surgery, the activation of the neuroendocrine system results in the release of cytokines and hormones, which induce systemic leukocyte alterations affecting NLR [ 28 ]. In our study, the mean cardiopulmonary bypass time was 78.0 ± 32.3 min, and although the aortic cross-clamp time was not recorded, it was estimated to be around 20% less than the time needed for extracorporeal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in cardiac surgery patients, besides the operational stress itself, the additional use of the stressful extracorporeal circuit triggers an unavoidable major immune response, accelerated through the contact of the blood products and the surfaces of the CPB tubes. Additionally, during anesthesia and surgery, the activation of the neuroendocrine system results in the release of cytokines and hormones, which induce systemic leukocyte alterations affecting NLR [ 28 ]. In our study, the mean cardiopulmonary bypass time was 78.0 ± 32.3 min, and although the aortic cross-clamp time was not recorded, it was estimated to be around 20% less than the time needed for extracorporeal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to these studies, we found a positive correlation between Tp-e interval, Tp-e/QT ratio and NLR, CRP, and ESR values. NLR is de ned as the ratio of the absolute neutrophil and lymphocyte count, which is a in ammatory marker that is signi cantly associated with elevated levels of proin ammatory cytokines [21] . Therefore, it can serve as a valid biomarkers of in ammation and alone or along with other markers to aid in the management of various acute and chronic diseases [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers serve as measurable indicators of biological processes and conditions, holding the potential to refine psychiatric care. , Linking clinical symptoms with underlying pathophysiology can enhance diagnostic accuracy, identify at-risk individuals, and predict treatment responses . However, the complexity of human cognition, potential cognitive biases, mental health stigma, and the subjectivity of psychiatric symptoms limit their role in everyday psychiatric practice …”
Section: Types Of Biomarkers In Psychiatrymentioning
confidence: 99%